![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
解下列方程:(1)4-8x=3-11x;(2)13(6x-3)=13x-6;(3)y+43?y+5=y+33?y?22;(4)x0.2?0.5x+10.3=
解下列方程:(1)4-8x=3-11x;(2)13(6x-3)=13x-6;(3)y+43?y+5=y+33?y?22;(4)x0.2?0.5x+10.3=1....
解下列方程:(1)4-8x=3-11x;(2)13(6x-3)=13x-6;(3)y+43?y+5=y+33?y?22;(4)x0.2?0.5x+10.3=1.
展开
展开全部
(1)-8x+11x=3-4,
3x=-1,
x=-
;
(2)6x-3=x-18,
5x=-15,
x=-3;
(3)2(y+4)-6y+30=2(y+3)-3(y-2),
2y+8-6y+30=2y+6-3y+6,
-3y=-26,
y=
;
(4)3x-x-2=0.6,
2x=2.6,
x=1.3.
3x=-1,
x=-
1 |
3 |
(2)6x-3=x-18,
5x=-15,
x=-3;
(3)2(y+4)-6y+30=2(y+3)-3(y-2),
2y+8-6y+30=2y+6-3y+6,
-3y=-26,
y=
26 |
3 |
(4)3x-x-2=0.6,
2x=2.6,
x=1.3.
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询